RAFT polymers for protein recognition - Tominey, Alan F.; Liese, Julia; Wei, Sun; Kowski, Klaus; Schrader, Thomas; Kraft, Arno (Beilstein Journal of Organic Chemistry, 2010)
A new family of linear polymers with pronounced affinity for arginine- and lysine-rich proteins has been created. To this end, N-isopropylacrylamide (NIPAM) was copolymerized in water with a binding monomer and a hydrophobic comonomer using a living radical polymerization (RAFT). The resulting copolymers were water-soluble and displayed narrow polydispersities. They formed tight complexes with basic proteins depending on the nature and amount of the binding monomer as well as on the choice of the added hydrophobic comonomer.
Keywords: electrostatic interactions; hydrophobic effect; isothermal calorimetry; protein recognition; RAFT polymers